2012
DOI: 10.4103/0377-4929.94862
|View full text |Cite
|
Sign up to set email alerts
|

Role of C-erbB2 expression in gallbladder cancer

Abstract: We found complete membranous staining of C-erbB2 in 9.4% of GBC which was frequent in well differentiated and stage II to stage IV tumors. C-erbB2 tumors had longer median survival than C-erbB2 negative tumors. C-erbB2 is not involved early in the carcinogenetic process as none of the dysplasia showed expression. C-erbB2 over-expression may be considered as target for therapy in advanced stage of GBC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 3 publications
2
15
0
Order By: Relevance
“…The TT genotype of rs4979462 and rs6478106 was more frequent in the Her-2 (+) patients. According to researches involved Her-2 indicated that Her-2 could regulate cell growth and proliferation through many pathways in different diseases ( 32 ). It acts as a key marker in diagnosis and predicts the prognosis of cancers ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…The TT genotype of rs4979462 and rs6478106 was more frequent in the Her-2 (+) patients. According to researches involved Her-2 indicated that Her-2 could regulate cell growth and proliferation through many pathways in different diseases ( 32 ). It acts as a key marker in diagnosis and predicts the prognosis of cancers ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it can be hypothesized that some oncogene is associated with in Gallbladder cancer progression. In a study from India, C-erbB2 was frequently expressed in well differentiated and stage II to stage IV in about 9.4% of GBC cases[90]. A recent report showed HER2/neu overexpression occurred in 14% of the advanced gallbladder cancer cases, and this subgroup was expected to be benefited from HER2/neu pathway inhibitors[91].…”
Section: Genetic Alterations In Gbcmentioning
confidence: 99%
“…Existing data various greatly, despite of same grade and stage of the included study subjects. Table 4[97-101] and Table 5[54,66,75,84,86,90,102-180] are summarizing global and single gene expression studies reported in GBC respectively.…”
Section: Gene Expression Studies In Gbcmentioning
confidence: 99%
“…Ki67 was highly expressed in these poorly differentiated cases (mean MIB1 LI= 62) as compared to 21 in well differentiated ones (p= 0.000).Ki67 overexpression has been related to poor tumor differentiation in some of the previous studies as well. 6 CerbB-2 has been related to advanced tumor stage 7 in gall bladder adenocarcinomas. In our cases, 12 out of 16 cases (75%) which showed full thickness invasion, were positive for CerbB2 as compared to only 67% of those with muscular propria invasion.…”
Section: Discussionmentioning
confidence: 99%